Utilization of nature- identical flavor in the development of flavored fettucine - Corsame, Joseph Engelbert S.; Galvez, Flor Crisanta F. (2000., 2000)
ABSTRACT The study aimed to develop a garlic flavored fettucine with optimum amount of flavoring that will enhance the flavor of pasta and to determine the effect of flavoring-dough interaction on the quality characteristics of the pasta. In phase I, acceptable levels of flavoring incorporated to the pasta dough from preliminary study namely 0.2%, 0.5%, and 0.8% were produced in the laboratory scale. Objective ans sensory evaluation resulted to the selection of 0.5% garlic flavor incorporation. Utilizing the established conditions from the first phase, a bench-scale production flavored fettucine was performed to determine the efficiency of the process and formulation of the chosen level of garlic flavor in Phase II.Lower drying yield and product yield was observed due to losses when produced in bench-scale than in laboratory scale. In the last phase, results of the previous studies were verified with the control and revealed that 0.5% level of garlic flavor in the dough was significantly different from unflavored fettucine.
Thesis (BSFT)-- University of the Philippines Diliman.
Keywords: Pasta